What Are the Costs of Diagnostics and Treatment of Lyme Borreliosis in Poland? - Rogalska, Anna Maria; Pawełczyk, Olga; Solarz, Krzysztof; Holecki, Tomasz (Frontiers in Public Health, 2021)
Lyme borreliosis (LB) is a growing epidemiological threat in many areas of the world, including North America and Europe. Due to the lack of effective protection against this disease, it seems important to ensure a timely diagnosis for effective treatment and the prevention of serious health consequences. The aim of this study was to assess the costs of diagnosis and treatment of Lyme disease in Poland. The costs incurred for the medical payer were analyzed. The cost of hospitalization due to LB for one patient in 2018 was estimated to be 582.39 EUR, which constituted 53.10% of the average monthly salary of that year. In the analyzed period (2008–2018), the number of people treated by medical services due to Lyme disease increased, both in hospitalization and ambulatory specialist care. Although, the costs of hospitalization were the highest of the two, we noticed a change ratio between hospitalization and ambulatory specialist care in favor of the latter.